SPATIAL PATTERN OF ZOOPLANKTON BIOMASS IN THE GULF OF MONTIJO, PANAMA - Carlos E. Seixas G. (Tecnociencia, 2004)
The following study analyses the spatial pattern of zooplankton biomass in a seven inshore offshore stations between Puerto Mutis and Cébaco island on October of 1997. At each station triplicates of 150 l samples were collected using a 4-stroke self priming volute pump and filtered through an 80 um plankton net. The salinity increased of 9.7 ppt at Puerto Mutis to 30.3 ppt at Gobernadora Island whereas temperature remained constant at 29.5 ºC mean. Piñas and Puerto Mutis showed lower Secchi depths whereas higher values were found near Gobernadora. Copepods and nauplios comprised 90% of the catches. Zooplankton biomass was significantly higher at Piñas station (83.3 + 5.8 mg/ mt3) whereas lower values were registered south Leones (5.10 + 2.8 mg/mt3).